Religious Identities in Southeastern Europe: Pomaks in Greece and Bulgaria : Behind the State Valance - Ubiparipović, Stefan (Occasional papers on religion in Eastern Europe, 2017)
First, I will briefly explain the important events that have coincided or strongly influenced Pomak identity during the twentieth century. Several Greek and Bulgarian state policies will be mentioned for they served as fierce attempts to essentially change Pomaks. This segment here will focus on the events that occurred between the end of World War I and shortly before the fall of the Soviet Union. Next, this paper will focus on the period after the fall of communism in Europe and attempt to address the current state policies towards Pomaks. Bulgaria and Greece, as major Orthodox Christian countries, have distinct solutions for cooperating with minorities which reflect the strong or weak influence of Islam. Finally, I will conclude this paper by showing that the Muslim religious identity is to some extent relative and may individually and directly depends on the strict or loose state policies addressing minorities. Furthermore, the persistent role the state plays here has led to an uncertainty regarding clear Pomak identity. After all, it seems that the state has been successful in influencing Pomaks, resulting in this minority being completely different in these two countries, where they face contrasting existential and structural problems.